PENGARUH TIME BUDGET PRESSURE, KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA PROFESI SEBAGAI VARIABLE MODERASI - Anugrah, Ichsan Satya; Ilham, Elfi; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect of time budget pressure, competence and independence of the quality of the audit with professional ethics as a moderating variable (studies on public accounting firm in Medan, Padang and Batam). Public accounting profession is responsible for raising the level of reliability of the financial statements. population of this research is the independent auditors who worked at the firm in theMedan, Padang and Batam. Sample selection of this research is done by using purposive sampling method, consisting of 20 office accountant who has been out of Medan, Padang and Batam with 100 auditors as respondents, and were recovered with complete answers obtained from 70 respondents. And processed using SPSS software version 20.0. The analytical method used is multiple regression analysis and analysis moderated system (MRA.) coefficient of determination was 74.6%, in the case of adjusted R-square. The results of this study using multiple regression test stated time budget pressure and Independence effect on audit quality, competence is not effect on audit quality. While using moderated regression analysis test no variables that affect on audit quality with professional ethics as a moderating variable.Keyword : Time Budget Pressure, Independence, Competence, Audit Quality and professional ethics